2000
DOI: 10.1038/sj.leu.2401761
|View full text |Cite
|
Sign up to set email alerts
|

Frequent disruption of the RB1 pathway in diffuse large B cell lymphoma: prognostic significance of E2F-1 and p16INK4A

Abstract: In the present study, we analysed 34 de novo diffuse large B cell lymphoma (DLCL) from a population-based lymphoma registry for alterations of the RB1 pathway at the genetic (RB1 and CDK4) and protein (pRb, cyclin D1, cyclin D3, CDK4, and E2F-1) level. The results were correlated with the data from our previous studies of CDKN2A deletion and hypermethylation, other p53 pathway components, p27Kip1 expression, and proliferation, as well as with clinical outcome, including prognosis. We found aberrant pRb express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 44 publications
4
34
2
6
Order By: Relevance
“…This suggests a tendency for concurrent alteration of the cell cycle regulators p27, p53, and Rb or p16 in DLBCL. These findings are in keeping with previous immunohistochemical and/or molecular data that concurrent aberrations of p53 and Rb1 pathways are frequent in DLBCL, being reported in about 20 to 40% of these tumors (13,24,29,32). The concurrent disruption of growth control pathways may have implications in the cell cycle by abrogating the compensatory network that was proposed to exist between p53 and Rb1 pathways.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests a tendency for concurrent alteration of the cell cycle regulators p27, p53, and Rb or p16 in DLBCL. These findings are in keeping with previous immunohistochemical and/or molecular data that concurrent aberrations of p53 and Rb1 pathways are frequent in DLBCL, being reported in about 20 to 40% of these tumors (13,24,29,32). The concurrent disruption of growth control pathways may have implications in the cell cycle by abrogating the compensatory network that was proposed to exist between p53 and Rb1 pathways.…”
Section: Discussionsupporting
confidence: 92%
“…Group 3 is composed of simultaneous detection of low/null p27 expression, increased p53 expression, and decreased Rb or p16 expression (three alterations: 11 cases). lecular networks regulating the cell cycle in malignancies provides valuable information for the understanding of the impaired regulation of these networks and permits further insight into oncogenesis (11,15,17,19,23,24,26,29,34,36). This approach was adopted in the present study to analyze the expression of p27 in relation with components of the p53 and Rb1 growth control pathways and the status of proliferation in 80 cases of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous promising cellular targets and assays have been identified, such as p53 [9,20], p16 INK4A [21], bcl-2 [22,23], bcl-6 [23,24], and gene expression profiling [25,26], none of these have gained the level of acceptance required to be routinely used for risk stratification in trials and other clinical settings. Until such biology-based markers have been validated and standardized, clinical factors will continue to be the foundation of prognosis assessment in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, several studies have reported the clinical relevance of some genetic lesions of B-DLCL, including gross rearrangements of BCL-6 and BCL-2 or alterations of tumor suppressor genes involved in RB1 and p53 pathways. 3,4,7,[19][20][21][22][23] Because some BCL-6 gene mutations have been suggested to deregulate the BCL-6 expression, 24 the presence of BCL-6 mutations may identify B-DLCL patients with possibly different biological behavior and clinical outcome. To date, however, the clinical relevance of BCL-6 mutations in B-DLCL patients has not been analyzed thoroughly.…”
Section: Introductionmentioning
confidence: 99%